Searching for the neural correlates of emotional intelligence: a systematic review - Martín-Aguiar,Víctor; Fernández-Berrocal,Pablo; Megías-Robles,Alberto (PeerJ, 2026)
The concept of emotional intelligence (EI) has gained significant interest in the scientific community in recent years. Despite its demonstrated impact on social and personal functioning, the neural bases underlying EI remain poorly understood. This study aimed to conduct a comprehensive systematic review of the existing literature on the neural correlates of EI. The search was conducted in Web of Science, Scopus, PsycINFO, and PubMed databases. A total of 849 studies were initially identified (after duplicates were removed), of which 34 met the inclusion criteria and were selected for the final synthesis. These studies employed various brain mapping techniques, including lesion studies, grey and white matter structural magnetic resonance imaging (MRI), task-based functional magnetic resonance imaging (fMRI), resting-state fMRI, and electroencephalogram (EEG). The findings of this review suggest that EI is supported by a complex and widespread brain network primarily implicated in the integration of cognitive and emotional processes, with significant involvement of structures commonly linked to social cognition. The literature mainly emphasized the role of the insula, ventromedial prefrontal cortex, orbitofrontal cortex, cingulate cortex, and amygdala in conjunction with brain networks comprising these areas, such as the somatic marker circuitry and the social cognition network. Other brain regions, including the dorsolateral prefrontal cortex, cuneus, precuneus, fusiform gyrus, superior temporal gyrus, cerebellum, parahippocampal gyrus, inferior frontal gyrus, frontopolar gyrus, superior parietal lobule, and superior longitudinal fasciculus (SLF) were also frequently mentioned. However, further research is needed to clarify the roles of some of these regions in EI. Limitations and future lines of research are discussed.
Keywords: Emotional intelligence; Systematic review; Neural correlates; Brain; MRI; fMRI; EEG